We're not from here - Rodkey, Geoff, 1970- (Crown Books for Young Readers, 2019)
"After a year on Mars, a young boy and his family migrate to the planet Choom, but the inhabitants of Choom, the Zhuri, who look like giant mosquitoes, don't really like humans and it up to the boy and his family to change their minds if they hope to survive." --